South Asian Digital Humanities Then and Now. Issue 3 (3rd July 2019) - Risam, Roopika; Gairola, Rahul K.
Abstract: The introduction to this special issue of South Asian Review assesses the history and present of South Asian studies and digital humanities. The essay begins by examining the South Asian Literary Association's early support for this scholarship, both through conferences panels and publications. It further details the emergence of initiatives such as the Digital Humanities Alliance of India (DHAI) that have contributed to research at the nexus of digital humanities and South Asian studies, as well as foundational digital humanities projects at these interstices. This introduction further situates South Asian digital humanities as an intervention in postcolonial digital humanities that expands, challenges, and complicates both South Asian technospaces and digital notions of home. The essay concludes with summaries of articles in the special issue, arguing that they demonstrate the possibilities of scholarship that bridges digital humanities and South Asian studies.